Recommendations for athletes to vaccinate against SARS-CoV-2 - Meyer, T.; Wolfarth, B.; Gärtner, B. (Deutsche Zeitschrift für Sportmedizin, 2021)
Summary After prioritization of populations w ith risk factors for severe courses of Covid-19 ("Corona") and occupational groups w ith a high number of close contacts w ith patients and other human beings, from now onward (performance-oriented) athletes w ill be considered for vaccination. ›Recommendations for vaccinations in this target group can be different from the ones for the general population in some aspects. However, there are only very few scientifically valid findings that may guide vaccinating medical doctors. ›This article summarizes available evidence and formulates recommendations for vaccinations in (high-performance) athletes.